Symposium 2: A doctoral researcher community on Twitter: An actor-network explication of #PhDchat - Keefer, Jeffrey M. (Proceedings of the International Conference on Networked Learning, 2014)
Late in 2010, a small group of postgraduate students discussed meeting on Twitter to discuss areas of interest to doctoral students. This developed into the hash tag #phdchat, which began informally with synchronous discussions on Wednesdays at 19.30 GMT, loosely focused around topics voted upon by anybody wishing to participate. The concept expanded to include people, primarily doctoral students, who discussed areas of shared interest such as motivations for doing a PhD or analysing data, along with various technologies of interest. From the time #phdchat Tweets began to be tracked to the time Twitter limited API use a few months later, there were 4,876 individual Tweets using the #phdchat tag. The 10 most active Tweeters using the tag during this period accounted for 52% of all the Tweets, even though there were 362 unique participants contributing at least once during this period. What did they talk about? While this seems a natural question with such intensive users, it may be a limiting question to consider, as it only looks at the surface result of the phenomenon, rather than at what held this informal network together. Instead, this research takes its inspiration from Latour’s notion that we need “to follow the actors themselves” (2005, p. 12), seeking to “avoid imposing our own views about what is right or wrong, or true and false” when considering social and technical interactions without distinguishing between human or non-human actors (Law & Callon, 1988, p. 284). The assembled bursts of Twitter activity is the result of the contributions of this active group of participants, with the central assembly being the hashtag #phdchat itself. This tag itself will be followed during this period of time, explicating how and in what ways the participation in the synchronous and asynchronous Twitter chats moved and enlisted other actors to bring meaning and support to those involved. This research will be presented as an interactive Pecha Kucha, with participants invited to use a Twitter tag during the session to focus on the issues raised and responses shared amongst those present and distant to the symposium.